O pewnej metodzie prognozowania przewozów w gospodarce - Acedański, Jan (A Prediction Method of Transport of Goods in the Economy, 2006)
The paper presents a simple method of goods transport volume prediction. Global freight volume was estimated on the bases of extrapolating transport absorption coefficient, whereas cargo intermodal division was modelled using homogenous Markov chain. Conditional general least square method was applied to estimate transition matrix from macrodata. As a result of proposed method forecasts of global freight volume in Poland and its intermodal division for years 2005-2006 were calculated. An attempt to estimate ex ante mean errors of prediction was also made.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 19-27